DNA Instability in premature aging - Cox, L; Boubriak, I (Nova Science Publishers, Inc., 2012)
DNA damage accumulates with increased chronological age and may contribute to both cell senescence and cancer. However, the importance and role(s) of DNA damage in promoting ageing is difficult to analyze experimentally at the molecular level since ageing results from a complex interplay of genetic and environmental factors. Premature human ageing syndromes offer a route to determining the molecular basis of at least some of the changes in DNA associated with normal ageing, as they are caused by mutation of individual genes whose protein products can be characterized in vitro. Furthermore, experimental manipulation of DNA stability may permit analysis of the contribution of DNA damage to the ageing process. Here, we assess the types of DNA instability observed in premature human ageing, particularly progeroid Hutchison Guilford Progeria and Werner's syndrome, and experimental models of these. The role for RecQ helicases and cognate exonucleases in maintaining DNA stability and preventing premature ageing is discussed in the context of studies in vitro and in model organisms. We conclude that it is by combining studies in various experimental systems that the true in vivo activities of these critical proteins can be elucidated. © 2010 Nova Science Publishers, Inc. All rights reserved.